1995
DOI: 10.1246/bcsj.68.2093
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric and 195Pt NMR Studies on Aromatic Ring Stacking between Nucleotides and Platinum DNA Intercalators

Abstract: Calorimetric and spectroscopic investigations have been carried out on the stacking interactions between nucleosides or nucleotides (NMP) and platinum DNA intercalators and other planar platinum(II) complexes with heteroaromatic ligands (L). Pt(L)(diamine) (L = 1,10-phenathroline (phen), its methyl and nitro derivatives, 2,2′-bipyridine; diamine = ethylenediamine (en), L-2,3-diaminopropionate) reacts with NMP (=adenosine 5′-monophosphate (AMP), guanosine 5′-monophosphate (GMP), inosine 5′-monophosphate (IMP), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…The deshielding may be a consequence of a small charge delocalization from the Pt atom due to the action of the above‐located large dipole of the Pt‐halogen moiety of the partner molecule. Similar deshielding of 195 Pt nucleus was also reported before for stacking of Pt‐containing heterocyclic compounds with nucleotides and also explained by charge delocalization in Pt atom , . Noteworthy, the solution study of the self‐association of related Pt complex of phenanthroline also resulted in antiparallel structure, qualitatively similar to that obtained in the present work.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The deshielding may be a consequence of a small charge delocalization from the Pt atom due to the action of the above‐located large dipole of the Pt‐halogen moiety of the partner molecule. Similar deshielding of 195 Pt nucleus was also reported before for stacking of Pt‐containing heterocyclic compounds with nucleotides and also explained by charge delocalization in Pt atom , . Noteworthy, the solution study of the self‐association of related Pt complex of phenanthroline also resulted in antiparallel structure, qualitatively similar to that obtained in the present work.…”
Section: Resultssupporting
confidence: 91%
“…0.3 ··· 0.4 ppm, are consistent with the ring‐current effect originating from diamagnetic shielding induced by delocalized aromatic π‐electrons circulating around the aromatic moieties of the molecules, located above each other inside a dimer . This configuration is possible only for the face‐to‐face orientation of the molecules in aggregates , …”
Section: Resultsmentioning
confidence: 99%
“…13 The adduct formation between planar Pt(II) complexes, Pt(DA)(L') (L' = ethylenediamine or amino acids), and mononucleotides was revealed to be enthalpically driven mainly through stacking interactions by the relevant thermodynamic parameters 14 and decrease the electron density of the Pt(II) center as seen from and the downfield shift of the 195 Pt NMR signal. 15 The adduct stability sequence due to DA,3,4,7,10-phenanthroline > 1,10-phenanthroline ≈ 5-nitro-1,10-phenanthroline, reflected the effects of the DA substituents on stacking. In this connection, Kohzuma et al reported that the Cu center of the plastocyanin from a fern Dryopteris crassirhzoma has a phenylalanyl residue stacked with a coordinated histidine (His90) and, probably as a result of this, exhibits a higher redox potential than that of higher plant plastocyanins.…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H NMR spectra were recorded from freshly prepared solutions of the complexes at concentrations of 1, 3,5,10,15,20,25,35,45 and 55 mM in D 2 O containing the internal reference and NaCl (100 mM).…”
Section: H Nmr Studies Of the Self-association Of Ruthenium(ii) Commentioning
confidence: 99%
“…The planar aromatic drugs proflavine and acridine orange, which are well known to be strong DNA intercalators, [6] self-associate in aqueous solutions via stacking interactions [7]. Stacking interactions in solution also occurs for inorganic complexes possessing a planar aromatic 0162 [15] and other related Pt(II) complexes [16]. The ternary Ru(II) complex [Ru(phen) 3 ] 2+ selfassociates by a stacking interaction in aqueous solution, [17] but the mode by which this complex binds to DNA (either intercalative or electrostatic groove binding) is the subject of some debate [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%